Species diversity assessment for rodents (Rodentia) in Hoang Lien national park, Sapa, Lao Cai, Vietnam - Duc, Nguyen Minh; Trang, Le Quynh; Tam, Nguyen Minh (Academia Journal of Biology, 2017)
22 rodent species were collected in 5,644 traplights in 22 transects in Hoang Lien National Park during two years (2014-2015). Some were common to include Niviventer confucianus, N. fulvescens, N. bukit and Tamiops sp., but many species such as Ratufa bicolor, Petaurista sp., Callosciurus sp., Dremomys sp. Hytrix sp., Typhlomys chapensis were rare to be collected. There varied the number of species among forest strata. The overstorey mainly contained the flying squirrels (Petaurista sp.) and tree squirrels of Callosciurus sp. and Ratufa sp., while the understorey and shrubs layer contained the large number of species in Callosciurus, Tamiops, Dremomys, Niviventer, Rattus and Hytrix, Rhizomys having their own habitat preference under the ground, where bamboo roots are their food. Three collected species; Typhlomys chapensis, Micromys minutes and Callosciurus inornatus were listed in 2013 IUCN Red List of threatened animals. T. chapensis distributed very narrowly. This species was found only in primary forests at >2400 m elevation. Relative abundance of the rodent species was very low. Reduced and fragmented habitats together with hunting pressure threatened to most animals in the park. Our data indicated that population sizes of all squirrels, porcupines were heavily reduced in relation to high hunting pressure and their disturbed habitats. Received 23 November 2016, accepted 20 December 2016